The work of art : how something comes from nothing - Moss, Adam (Penguin Press, 2024)
"From former editor-in-chief of New York magazine Adam Moss, a collection of illuminating conversations examining the very personal, rigorous, complex, and elusive work of making art. What is the work of art? In this guided tour inside the artist's head, Adam Moss traces the evolution of transcendent novels, paintings, jokes, movies, songs, and more. Weaving conversations with some of the most accomplished artists of our time together with the journal entries, napkin doodles, and sketches that were their tools, Moss breaks down the work-the tortuous paths and artistic decisions-that led to great art. From first glimmers to second thoughts, roads not taken, crises, breakthroughs, on to one triumphant finish after another"--